Novel biocompatible ionic liquids based on gluconate anion - Costa, Alexandra (2015)
A sustainable organic synthetic methodology for the preparation of novel biocompatible ionic liquids (ILs) based on gluconate anion has been developed. Four functionalized methylimidazolium cations were efficiently combined with gluconic acid by acid-base neutralization reactions. All salts were obtained as RTILs in high yields (92–98%) and in high purity levels. Proton Nuclear Magnetic Resonance (1H NMR) studies had proved the correct cation/ anion proportion (1:1) and their chemical stability. These novel gluconate ILs can be applied for chemistry, material science, and medicine areas.